CATCHES LOADING AND UNLOADING ACTIVITES POTENTIAL HAZARDS AT KEJAWANAN FISHING PORT - Imron, Mohammad; Taurusman, Am Azbas; Yusfiandayani, Roza; Bahiya; Astuti, Lussy; Tiara (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
Activities conducted at the Kejawanan Nusantara Fishing Port include landing of fish including loading and unloading of catches that have the highest potential for work accidents. Work accidents can result in losses such as delays in loading and unloading activities. Potential hazards can arise due to the lack of awareness of the parties involved in the loading and unloading operation process, including the authorities in handling the prevention and control of work accidents that occur. This study aims to describe loading and unloading activities, identify potential hazards, and develop recommendations and risk mitigation. The research was conducted in October-November 2024 at Kejawanan VAT, Cirebon. The analysis used was descriptive with the Hierarchy Task Analysis (HTA) and Job Safety Analysis (JSA) methods. The results of the study identified six main stages namely pre-unloading, unloading activities, post-unloading, pre-loading, loading activities, and post-loading which included 62 potential hazards, categorized as 25% non-hazardous, 33% mild, 17% medium, 19% severe, and 6% potentially fatal. Prevention of work accidents can be done through increasing awareness of the use of Personal Protective Equipment (PPE), certification of transportation drivers to prevent fatal accidents, and strict supervision by port managers. This effort is expected to improve work safety in every loading and unloading activity at Kejawanan PPN. Key words: HTA, JSA, loading and unloading, PPN Kejawanan, work safety